The thermal conductivity of the Earth's core and implications for its thermal and compositional evolution - Ohta, Kenji (Natl Sci Rev, 2020)
Determining the thermal conductivity of iron alloys at high pressures and temperatures are essential for understanding the thermal history and dynamics of the Earth's metallic cores. The authors summarize relevant high-pressure experiments using a diamond-anvil cell and discuss implications of high core conductivity for its thermal and compositional evolution.